Pharmacokinetic Study and Metabolite Identification of 1-(3'-bromophenyl)-heliamine in Rats - Ruqi Xi; Rahima Abdulla; Miaomiao Zhang; Zhurakulov Sherzod; Vinogradova Valentina Ivanovna; Maidina Habasi; Yongqiang Liu (MDPI AG, 2022)
Tetrahydroisoquinolines have been widely investigated for the treatment of arrhythmias. 1−(3'−bromophenyl)−heliamine (BH), an anti−arrhythmias agent, is a synthetic tetrahydroisoquinoline. This study focuses on the pharmacokinetic characterization of BH, as well as the identification of its metabolites, both in vitro and in vivo. A UHPLC−MS/MS method was developed and validated to quantify BH in rat plasma with a linear range of 1-1000 ng/mL. The validated method was applied to a pharmacokinetic study in rats. The maximum concentration Cmax (568.65 ± 122.14 ng/mL) reached 1.00 ± 0.45 h after oral administration. The main metabolic pathways appeared to be phase-I of demethylation, dehydrogenation, and epoxidation, and phase II of glucuronide and sulfate metabolites. Finally, a total of 18 metabolites were characterized, including 10 phase I metabolites and 8 phase II metabolites. Through the above studies, we have gained a better understanding of the absorption and metabolism of BH in vitro and in vivo, which will provide us with guidance for future in-depth studies on this compound.